PENGGUNAAN BUKU TEKS SEJARAH PADA PEMBELAJARAN SEJARAH INDONESIA DI KELAS X MIPA SMA NEGERI 2 PONTIANAK - Kurnia, Dini (Kurikula : Jurnal Pendidikan, 2024)
The research aims to know about the use of textbooks history in IndonesianHistorical learning in class X MIPA of Senior High School 2 Pontianak. The method in thisresearch is descriptive qualitative. This research used three informants, the curriculum viceprincipal, history teacher, and students. Data collection techniques were observation, interview,and documentation. Data analysis used data reduction techniques, data presentation, anddrawing conclusions. The results of this research show that first, the use of history textbooks byteacher is as an material to support the process of learning, while for students as an referencematerial. Second, the strategy used by teacher in using history textbooks is explaining,summaring, and group discussions, while the strategy used by students is noting importantpoints. Third, the obstacles experienced by teacher in using textbooks are external factorsnamely the transition from online to offline, while the obstacles experienced by students areinternal factors namely not understanding certain parts of textbooks.